2022
DOI: 10.1080/22221751.2022.2125347
|View full text |Cite
|
Sign up to set email alerts
|

The modulatory action of C-Vx substance on the immune system in COVID-19

Abstract: The modulatory effect of C-Vx, a novel therapeutic agent, on the immune system of COVID-19 patients was investigated. The functions of T and NK cells of COVID-19 patients with different disease severity were evaluated by flow cytometry in response to C-Vx stimulation. The levels of pro- and anti-inflammatory cytokines were detected by multiplex assay in supernatants after cell culture with C-Vx. Bradykinin, IRF3, and IFN-α levels were also measured by ELISA in the presence or absence of C-Vx stimulation. As a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…As a result of receptor interaction, various transcription factors such as the intracellular Nuclear Factor Kappa-light-chain-enhancer of activated B cells (NFκB) are activated and cause the expression of pro-inflammatory factors. In COVID-19 disease, increased levels of proand anti-inflammatory cytokines and chemokines, which induce a high degree of immune response that causes cytokine release syndrome (CRS), were reported [18]. Many studies showed that there were defects also in the functions of innate and adaptive immune cells and reduced cell numbers in patients infected with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of receptor interaction, various transcription factors such as the intracellular Nuclear Factor Kappa-light-chain-enhancer of activated B cells (NFκB) are activated and cause the expression of pro-inflammatory factors. In COVID-19 disease, increased levels of proand anti-inflammatory cytokines and chemokines, which induce a high degree of immune response that causes cytokine release syndrome (CRS), were reported [18]. Many studies showed that there were defects also in the functions of innate and adaptive immune cells and reduced cell numbers in patients infected with COVID-19.…”
Section: Introductionmentioning
confidence: 99%